Other race effect on amygdala response during affective facial processing in major depression. (1st January 2018) - Sankar, Anjali; Costafreda, Sergi G.; Marangell, Lauren B.; Fu, Cynthia H.Y.
Highlights: Neural correlates underlying the ORE is not well examined in mental health disorders. We investigated the impact of ORE on amygdala responses in major depression (MDD). ORE is associated with increased amygdala activations in both MDD and matched controls. ORE related amygdala responsivity may confound neural responses to facial stimuli. The implications of ORE on interpersonal functioning in MDD require further study. Abstract: Objective: The other race effect, also known as own race bias, refers to the enhanced ability to recognize faces belonging to one's own race relative to faces from another race. The other race effect is associated with increased amygdala response in healthy individuals. The amygdala is a key node in emotion processing which shows impaired functioning in depression and has been proposed to be a marker of depressive state. We investigated the impact of the other race effect on amygdala responses in depression. Methods: Participants were 30 individuals with major depression (mean age 39.4 years) and 23 healthy individuals (mean age: 38.8 years) recruited from the community. Participants were Asian, Black/African American and Caucasian. During a functional MRI scan, participants viewed Caucasian faces which displayed a range of sad expressions. A region of interest analysis of left and right amygdala responses was performed. Results: Increased bilateral amygdala responses were observed in response to the Caucasian face stimuli in participants who were Asian or Black/African American as compared to Caucasian participants in both healthy individuals and individuals with major depression. There was no significant group by race interaction effect. Conclusions: Increased amygdala responses associated with the other race effect were evident in both individuals with major depression and in healthy participants. Increased amygdala responses with the other race effect is a potential confound of the neural correlates of facial processing in healthy participants and in mental health disorders. The implications of the other race effect on impairments in interpersonal functioning in depression require further investigation.